Evaluation of in vitro Interaction of Metformin with Ibuprofen in Aqueous Medium - Saha, Shuvashis; Begum, Rehana; Rahman, Asma; Sultan, Md Zakir; Amran, Md Shah; Hossain, Md Amjad (Bangladesh Pharmaceutical Journal, 2015)
The purpose of the present study was to investigate the in vitro complex formation and to study the nature and strength of complexes which could be formed due to interaction of metformin with ibuprofen. Metformin is an antidiabetic drug and ibuprofen is a non steroidal anti-inflammatory drug (NSAID). The in vitro interaction of metformin with ibuprofen was studied at room temperature and at different pH conditions. The studies were performed by UV-Visible spectrophotometry, conductometry and reversed - it was phase high performance liquid chromatography (RP-HPLC). It was found that metformin formed stable 1:1 complex with ibuprofen. The interaction may greatly influence the activity of these molecules. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22303 Bangladesh Pharmaceutical Journal 16(2): 189-194, 2013